Apropriação de conceitos da saúde única como ferramenta educacional para a formação interprofissional em saúde - Fernandes, Bárbara Costa (2024)
Introduction: The One Health approach is widely recognized by various national and international organizations for its potential to prevent future pandemics, reduce the burden of endemic zoonotic and neglected tropical diseases, mitigate antimicrobial resistance, and promote health sustainably at the human-animal-environment ecosystem interface on a global, regional, and national level. However, a major challenge in operationalizing this concept is the inadequate training of professionals. In Brazil, there are educational and research institutions that have acknowledged the need to include One Health topics as a transversal theme in health education. This project aims to contribute to One Health practices within an interprofessional health education setting at a public university in the southeastern region of Brazil, starting with small groups of future health professionals but with the potential for replication beyond traditional educational environments.Objective: In light of the new challenges in public health and the need to adapt educational processes to new global realities, this project aims to assess the knowledge of students at the Health Sciences Center (CCS) of the Federal University of Espírito Santo (UFES) before and after adopting the One Health approach. Method: This is an interventionist, and descriptive study to be conducted at CCS/UFES. Data collection was based on survey research concepts and characterized through a semi-structured questionnaire developed by the researcher. Results: The study involved 47 health students from UFES, predominantly women, with an average age of 23 years and nine months. These students, from seven different courses, collaborated to promote interprofessionalism and the implementation of One Health in the curriculum. The educational intervention showed significant differences between the pre- and post-intervention stages, with an increase in achieving learning objectives. The study emphasizes the importance of Interprofessional Education in preparing health professionals to face global challenges such as climate change and community health, as advocated by international organizations like the UN and the Global Consortium on Climate and Health Education. The experience also addressed competencies such as collaborative leadership and conflict resolution, essential for the practice of One Health. Conclusions: This study provided contributions to the theory and practice of One Health in an interprofessional health education environment at a public university with potential for replication. It highlighted the effectiveness of integrating One Health into the health courses' curriculum. Training professionals to address global challenges such as climate change and global health, as recommended by international organizations like the United Nations and the Global Consortium on Climate and Health Education, strengthens the ability to tackle multidimensional problems. Additionally, it fosters closer relationships and the exchange of experiences among different knowledge areas within the educational and research institution